1995
DOI: 10.1038/376737a0
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine kinase PYK2 involved in Ca2+-induced regulation of ion channel and MAP kinase functions

Abstract: The protein tyrosine kinase PYK2, which is highly expressed in the central nervous system, is rapidly phosphorylated on tyrosine residues in response to various stimuli that elevate the intracellular calcium concentration, as well as by protein kinase C activation. Activation of PYK2 leads to modulation of ion channel function and activation of the MAP kinase signalling pathway. PYK2 activation may provide a mechanism for a variety of short- and long-term calcium-dependent signalling events in the nervous syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

54
1,440
13
4

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,319 publications
(1,511 citation statements)
references
References 45 publications
54
1,440
13
4
Order By: Relevance
“…Additionally, LNCaP cells express an inactive form of FAK (Tremblay et al, 1996). PYK2-mediated functions are carried out by activating multiple downstream signaling molecules, including ERK/ MAPK (Lev et al, 1995), p38/MAPK (Pandey et al, 1999), c-Src (Dikic et al, 1996) and paxillin (Li and Earp, 1997), which lead to the differential regulation of cell adhesion in different cell types. While elevated ERK/MAPK, p38/MAPK and c-Src activities are correlated with increased PYK2 activity and enhanced adhesion in C-81 as well as PYK2 cDNA-transfected C-33 cells (Supplementary Figure 1A and 2), only ERK/ MAPK activity was consistently reduced by expressing the Y402F or the K457A-PYK2 mutants in C-81 cells, correlated with a decreased adhesion (Figure 6, Supplementary Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, LNCaP cells express an inactive form of FAK (Tremblay et al, 1996). PYK2-mediated functions are carried out by activating multiple downstream signaling molecules, including ERK/ MAPK (Lev et al, 1995), p38/MAPK (Pandey et al, 1999), c-Src (Dikic et al, 1996) and paxillin (Li and Earp, 1997), which lead to the differential regulation of cell adhesion in different cell types. While elevated ERK/MAPK, p38/MAPK and c-Src activities are correlated with increased PYK2 activity and enhanced adhesion in C-81 as well as PYK2 cDNA-transfected C-33 cells (Supplementary Figure 1A and 2), only ERK/ MAPK activity was consistently reduced by expressing the Y402F or the K457A-PYK2 mutants in C-81 cells, correlated with a decreased adhesion (Figure 6, Supplementary Figure 1B).…”
Section: Discussionmentioning
confidence: 99%
“…In these cellular settings Pyk2, a focal adhesion kinase related tyrosine kinase independently activated by Ca 2+ and phorbol esters (Lev et al, 1995), has recently been placed upstream of receptor tyrosine kinases in the signaling pathway from G q/11 -coupled receptors to ERKs (Eguchi et al, 1999;Solto , 1998). To better understand mitogenic signaling by G q/11 -coupled receptors in SCLC cells, a detailed analysis of the role of receptor tyrosine kinases like c-kit and of non-receptor tyrosine kinases such as Pyk2 should be enlightening in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in cell types such as CHO, it has been observed that Ga q can activate an ERK-mediated proliferative pathway through a PKC-dependent but Ras-independent mechanism (Figure 1). However, in other cell types such as the rat vascular smooth muscle and NIH3T3 cells, Ga q appear to activate ERK through a novel pathway involving proline-rich tyrosine kinase-2 (Pyk2) and Ras (Lev et al, 1995;Bourne, 1995). This pathway appears to be activated by the IP 3 generated by the activation of PLC.…”
Section: Ga Q the Conditional Oncogenementioning
confidence: 99%